AUW TJOEI LAN SEBAGAI REPRESENTASI PERJUANGAN TRIPLE DISCRIMINATION SEJARAH PERGERAKAN NASIONAL REPUBLIK INDONESIA - Jihan Jauhar Nafisah (Pusat Studi Gender dan Anak (PSGA), Universitas Islam Negeri Syarif Hidayatullah, 2022)
Abstract. This article describes the ethnic Chinese as a minority who had to go through various discriminations, especially violence against women, thus giving birth to a new female figure, namely Auw Tjoei Lan during the national movement. The researcher hopes that this figure can inspire multicultural-based history learning in schools. So that students can understand that the Indonesian struggle is not only carried out by men. Many women have contributed to achieving the unity of Indonesia. In addition, the concept of women's emancipation tends to only apply to indigenous women such as Raden Ajeng Kartini and Dewi Sartika. Whereas ethnic Chinese are also part of Indonesian society and are involved in Indonesia's independence efforts. The formulation of the problem in the study of this article is